Exploring supply chain managers' complex perceptions of dynamic capabilities for digital transformation - Mario Dobrovnik; David M. Herold; Sebastian Kummer (Digital Business)
Although the use of new digital technologies is an increasingly important topic for supply chain managers, existing literature is limited on what specific capabilities are perceived to be important for a successful transition to digital supply chains, in particular from a managerial perspective. In response, this study examines how supply chain managers perceive the importance and interconnections of specific digital capabilities for digital transformation. Based on a digital capability framework, we surveyed supply chain managers in Austria and Germany. The sample consisted of two groups, comprising senior managers from logistics service providers and from manufacturing companies. Decision-Making Trail and Evaluation (DEMATEL) was used to evaluate the managers' perceptions of the importance of the enablers and their relationships between capabilities. Our findings show that senior managers in the supply chain domain perceive interactions between dynamic capabilities as a complex and highly interconnected system, rather than discrete and linear. Digital mindset crafting, digital scenario planning and improving digital maturity were identified as the most relevant capabilities in both subsamples, while digital sensing was considered to be the most relevant capability at the construct level, followed by digital seizing and digital transforming. Furthermore, supply chain managers in manufacturing perceived that digital capabilities were more developed in their industry. We anticipate that our findings will inform and guide capability-building in dynamic corporate settings. This study is one of the first to empirically assess how supply chain managers perceive the importance of specific digital capabilities and their interdependencies for digital transformation.